IDENTIFIKASI PENYESUAIN GAYA HIDUP DIKARENAKAN KEBISINGAN PESAWAT DI BANDARA INTERNASIONAL AHMAD YANI DAN SEKITARNYA - Abdusalam Masaud; Kismartini Kismartini; Haryono S Huboyo (Universitas Sebelas Maret, 2014)
Noise is one of the most common items used by aircraft around the world , there are About 50,000 commercial flights each day around the word and 3 million people traveling . In the operational of aviation in Ahmad Yani International Airport Semarang , an airplane can make some noise. The noise is a sound that unwanted in a place and time scale, it can make some disturbance that influence human freshness and health. Particularly for Residents whom living very close by the airport such as Graha Padma and Tambakharjo. It is commonly believed that people adapt rather easily to noise. This research reviews the available data , finding little evidence that any adaptation occurs in community close by airport .however, is open to alternative interpretations. The present study, examining reactions noise effect from the airport daily operations on residents near by the airport and how they can adapting with the aircraft noise in them daily lifestyle .first of all , we measured the noise inside Graha Padma and Tambakharjo in 23 points using apparatus sound level meter, Taking into consideration different locations ,times and days . we classification this area into three , most affected area , affected area and low affected area according to the levels of noise .we took 30 random simples of people taking into consideration different times ,days , age, gender and distance. This study wants to suggest that the airport should take a new bigger role to minimize the noise and people whom living around the airport should follow some steps to adapting or avoid the aircraft noise. Keywords : Noise , community ,adaptation and Ahmad Yani Airport Semarang